Application of multi-objective optimization for TLP considering hull-form and tendon system. (1st April 2016) - Du Kim, Jeong; Jang, Beom-Seon
Abstract: The tension leg platform (TLP) is one of the conventional offshore oil- and gas-production structures. With the TLP, relatively small motion responses can be maintained, as most vertical wave loads are resisted by a tendon system consisting of multiple tendons, the high vertical stiffness of which makes possible the achievement of a quite low heave natural frequency. Notwithstanding this advantage, the TLP requires a complicated and time-consuming design process. In this study, a multi-objective optimization system for both the hull form and tendon system was developed. The maximum heave response and the total weight of the hull and tendons are formulated as objective functions. Five modules were developed to automate TLP modeling and performance assessment as the preliminary steps to optimization. In the first module, the panel and Morison models are automatically generated to model the hull form and tendon system based on predefined design parameters. Light weight and displacement at several stages are estimated in the mass estimation module based on surface area and hull volume. After generation of the hydrodynamic model, the motion response of a TLP is calculated by the commercial program DNV. WADAM (DNV software, 2013 ). The dynamic tension loads of the tendons are added to the restoring force matrix of motion equation, under the assumption that the tendons are linear springs. In the post process module, ultimate limit state (ULS) and fatigue limit state (FLS) assessment procedures are carried out. In the optimization module, multi-objective optimization by a simulated annealing (SA) method is performed. Thereby, eight different optimum solutions forming a Pareto set are obtained and compared with each other to determine their validity. Based on those solutions, the present study determined that the pontoon volume and the sectional area of the tendons dominantly affect the following objective values: the maximum heave response and the total weight of the hull and tendons. Highlights: Design of tension leg platform (TLP) is difficult to reach a feasible and superior design. This paper provides an optimization method for TLP in the consideration of hull form and tendons. A modeling and assessment procedure of TLP is developed to formulate the optimization problem. A total eight different optimum solutions are compared for their validity.